Predicting in vivo safety characteristics using physiochemical properties and in vitro assays. (September 2011) - Greene, Nigel; Song, Minghu
There is increasing pressure on the pharmaceutical industry to deliver safer and more effective medicines while constraining research and development costs. In order to meet these demands, the industry is looking for basic design principles in terms of physicochemical properties as well as the use of higher throughput in vitro assays to select and evaluate new molecular entities for further development. Recent advances in understanding the relationships between a chemical''s properties and its propensity for adverse events, as well as the development of new in vitro screening technologies, have enhanced our ability to potentially select molecules more likely to succeed in becoming drugs. However, these approaches are still limited by the availability of data and our lack of understanding of the mechanisms by which compounds can cause toxicity.